English Code-Switching in Indonesian Magazine Articles - Indah Dwi Cahayany; Akhmad Baihaqi (Journal of English Language Teaching and Cultural Studies, 2019)
The objective of this research was to analyze English code-switching in indonesian magazine articles. It was to to identify the types of the English-Indonesian code-switching in Gadis magazine no. 04 April 2017. The researcher used qualitative research. This main article consists of 10 subtopic articles. The writer collected the data by reading the Gadis magazine and underlined the English code-switching happened in the writing of the articles. The types of code-switching occured were inter-sentional switching accounted for 13% and intra-sententional switching accounted for 87%. The code-switching occured in the boundary of words, sentences, and combination of Indonesian word and English word in a sigle word. The conclusion of this research was code-switching is accepted by Indonesian people in society to convey their ideas or meaning or in this case, to attract readers.